Preparation of hybrid triple‐stimuli responsive nanogels based on poly(L‐histidine). Issue 9 (12th November 2015) - Bilalis, Panayiotis; Varlas, Spyridon; Kiafa, Aikaterini; Velentzas, Athanassios; Stravopodis, Dimitrios; Iatrou, Hermis
ABSTRACT: A series of novel multi‐responsive disulfide cross‐linked polypeptide nanogels has been synthesized by a one‐step ring‐opening polymerization process. The pH‐responsive core of the prepared nanogels was based on poly(L‐histidine), the difunctional N‐carboxy anhydride ofl ‐cystine (l ‐Cys‐NCA) was used as a reduction‐cleavable cross‐linking agent, while the outer hydrophilic corona was comprised of a poly(ethylene oxide) block. Extensive molecular characterization studies were conducted in order to confirm the formation of the desired polymeric nanostructures and also to prove their responsiveness to external stimuli within the physiological values of healthy and cancer tissues. Furthermore, the disruption of the disulfide‐bond linkages between the polymeric chains was achieved by the presence of the reductive tripeptide glutathione (GSH), leading to size variations that were monitored by dynamic light scattering (DLS) and size‐exclusion chromatography (SEC). "Stealth" properties of the formed nanostructures were examined by zeta potential measurements. The described nanogels are clearly promising candidates for drug delivery applications. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1278–1288 Abstract : Novel hybrid multi‐stimuli responsive nanogels consisting of a PEO corona and a disulfide cross‐linked PHis core were synthesized in order to be used as promising drug delivery systems. The dependence between the cross‐linker's ratio and pH‐sensitivity was evaluated and also the GSH responsiveness proving that these polymeric structures could be disrupted under intracellular‐mimicking conditions.